سیرت طیبہ کی روشنی میں مذاہب عالم کے مقدسات کی تکریم اور رعایت (شخصیات، مقامات، کتب، تہوار): Honoring and honoring the holy things of the world religions (persons, places, books, festivals) in the light of Sirat Tayyaba. - Dr. Muhammad Irfan, (Seerat Studies, 2023)
There is no doubt, that, this world is converted into a global village today. So, the problems of different nations are not individual anymore, rather, they have become a collective thing. An Issue that occurs anywhere in the world would disturb the whole world somehow. The sacredness of the religion is a highlight of these issues that can disturb peace globally. Every religion has some sacred things, which are always regarded as respectable by all. If anybody attempts to disgrace the sacredness of any other religion, his act is considered as enmity and outrage against this system. This study elaborates the status of religious symbols in the light of Seerat-ul-Nabi. The article brings to light various definitions and elaboration of religious symbols and sanctities. The study analyses the various incidents that occurred in the life of our Holy Prophet (PBUH) regarding disgrace towards the religious symbols to understand the importance of religious sanctities in the light of Seert-ul-Nabi.